ISLAMIC EDUCATIONAL THOUGHT - Mia Ananda Putri; Meuthia Putri (Proceeding International Seminar of Islamic Studies, 2022)
Thought comes from the root word which means the process, way or act of thinking, namely using reason to decide a problem by considering everything wisely. Thinking can be interpreted from two aspects, namely as a process and as a result of the first aspect, thinking as a process of reasoning phenomena and trying to find solutions wisely. Meanwhile, from the result of the ijtihad process of human efforts to solve lifes problems. Thinking is the result of intelligent effort (ijtihad) from the process of the mind and heart to see phenomena and try to find solutions wisely. The placement of the word islam after the word educational thinking in islamic teachings. The thought of education that is formulated appropriately and based on the teachings of islam (religion) is the thought of islamic education is an educational thought that is in accordance with islamic principles and vice versa which is produced by muslims.Keywords : Thought Concept, Islamic Education And Religion